Cinquante ans de production immobilière de bureaux à Bruxelles - Christian Dessouroux (Brussels Studies)
This article provides an overview of the spatial development of office building production in Brussels over the past fifty years. Due to the disappearance of agricultural and industrial jobs, most of the people who work in the Region now work in offices (two-thirds of the 724 000 workers). The continual spatial expansion of areas occupied by offices is symbolic of the development of the service sector as well as the economic prosperity of the capital, but is also an element of its fragility and complexity. The historical analysis of office building production reveals a spatial development which is centrifugal, asymmetrical and polycentric.The present study – initiated by the activities of the Review of office property (office monitoring centre) – was conducted in the framework of the collective work published by the Studies and Planning Department of the Ministry of the Brussels-Capital Region, entitled Bruxelles, ses bureaux, ses employés. It includes approximately twenty contributions, an original cartography and rich illustrations, and examines the many facets of a phenomenon which has greatly influenced the history of Brussels since the post-war years.